Owning our Professional Practice: Back to Basics. Issue 3 (May 2022) - Wisner, Kirsten
Abstract : Perinatal nurses have multiple options to keep up to date about the latest evidence and clinical practice standards and guidelines. Our maternity nursing expert, Dr. Wisner, offers suggestions including becoming a member of our professional organization, the Association of Women's Health, Obstetric, and Neonatal Nurses, becoming certified in one or more perinatal nursing or interdisciplinary certification processes through the National Certification Corporation, and establishing a process for routine review of evidence, guidelines, and standards from professional nursing and medical organizations that support perinatal care givers.